Enhanced Adaptive Mechanisms to Improve QOS in Distributed Multimedia Applications (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Recent advances in computer communications, especially highly interactivedistributed applications and those relying on the transfer of multimedia information and in particular, continuous media flows. It is essential that QoS is guaranteed in a system, considering distributed system area, the transport protocol and themultiservice network. Quality of Service (QoS) in distributed multimedia systems provides a unifying theme on which the functions and facilities of the new integrated standards can be constructed.Â  The objective of thispaper is tofocusonseveral QoS parametersat different levelsand Enhanced Adaptive Mechanismis proposed in order to improve the performance in distributed multimediaapplications.